2015
DOI: 10.3844/ajmsp.2015.31.39
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cultural Conditions for Production of Exopolysaccaride by <i>Halomonas marina</i> HMA 103 under Batch-Culture

Abstract: A moderately halophilic bacterium, Halomonas marina HMA 103 (MTCC 8968) accumulating intracellular polyesters also produced significant amount of exopolysaccharides (EPS) under batch-culture. Production of EPS by the bacterium was more or less parallel with the growth in modified basal synthetic medium. During growth, it produced 0.46 g/L of EPS after 50 h of incubation and was accompanied by the complete utilization of glucose from the medium. EPS production was maximum in 2% (w/v) glucose followed by sucrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Orsod et al (2012) also reported that the EPS extracted from marine bacteria showed absorption indicated alkenes, ketones, isocyanate and isothiocyanate groups, alcohols, ethers, esters carboxylic acids and phenols groups. Another study by Pal et al (2015) stated that the Fourier Transform Infrared (FTIR) spectrum of EPS produced by Halomonas marina HMA 103 showed distinct absorption peaks at 3424.2, 1638.7, 1122.9 and 622.3 cm -1 indicating the presence of free hydroxyl, phenyl or carbonyl groups of carbohydrate as was stated by Pal et al (2015).…”
Section: Chemical Analyses Of Eps Produced By Hsaccharevitansab2mentioning
confidence: 86%
“…Orsod et al (2012) also reported that the EPS extracted from marine bacteria showed absorption indicated alkenes, ketones, isocyanate and isothiocyanate groups, alcohols, ethers, esters carboxylic acids and phenols groups. Another study by Pal et al (2015) stated that the Fourier Transform Infrared (FTIR) spectrum of EPS produced by Halomonas marina HMA 103 showed distinct absorption peaks at 3424.2, 1638.7, 1122.9 and 622.3 cm -1 indicating the presence of free hydroxyl, phenyl or carbonyl groups of carbohydrate as was stated by Pal et al (2015).…”
Section: Chemical Analyses Of Eps Produced By Hsaccharevitansab2mentioning
confidence: 86%
“…The peak around 1643 cm − 1 indicates the C = O stretch of amides corresponding to amide C = O and C-N bending of protein and peptide amines that indicates the characteristic IR absorption of polysaccharides and this absorption peak concluded that there is an amino sugar (Qiang et al 2013). The C = C stretching vibration at 1643.27 cm − 1 might indicate a phenyl ring or the presence of conjugated carbonyl groups (Pal et al 2015). The absorption peak at 1414.02 cm − 1 confirms the presence of O = H bend of esters that could be assigned to C = O of the COO and C-O bond from COO- (Helm 1995).…”
Section: Chemical Composition and Characterization Of Purified Epsmentioning
confidence: 99%